Control of catalytic flow reversal reactor - Kariwala, Vinay (2009)
This paper deals with control of catalytic flow reversal reactors (CFRR) used for oxidation of greenhouse gases like methane. This system differs from conventional reactors as it is a discrete-event or hybrid system with the only available manipulated variable being the flow direction. For maintaining high conversion rate and safety reasons, closed loop control is required. We successfully implement and compare the performances of different techniques like logic control, scheduling and predictive control for safe operation of CFRR. We find that the performances of latter two schemes are almost equivalent.